Sit mī khrū, khrū mī sit : chīwit læ phonngān h̄æng ʻadīt kh̨ōng sinlapin h̄æng chāt sākhā thatsanasin (čhittrakam) Prayūn ʻUluchāda - N̨ō. Na Pāknam, 1928- (s.n., 2001)
Autobiography of a Thai artist, painter and sculptor also a writer popular as N̨ō. Na Pāknam.